La exigibilidad de los Convenios de Accionistas frente a la sociedad y el principio de relatividad contractual - Moore Murphy, Joyce (2020)
The following article will address the topic of why should the Peruvian General Corporations Law be modified, in order to specify in which cases a shareholders agreement can impose obligations on the company and in which cases it can only be opposable. Moreover, the author will proposes that the application of said law should be done through a systematic interpretation with the Civil Code.